The Upper Atmosphere of Uranus from Stellar Occultations. II. Revised Temperatures in the Upper Stratosphere and Lower Thermosphere - William R. Saunders; Michael J. Person; Paul Withers; Richard G. French; Chanita Tubthong (The Planetary Science Journal, 2024)
Measurements made by Voyager 2 during its flyby of Uranus in 1986 found warm stratospheric and hot thermospheric temperatures that cannot be explained by solar energy alone. This contributes to what is known as the “giant planet energy crisis”: there is a fundamental lack of understanding of the energy balance of giant planets in the solar system. Uranus, in particular, has the coldest stratosphere temperatures, the hottest thermospheric temperatures, and the weakest internal heat flux of all four giant planets. Moreover, the Voyager 2 temperature measurements are at odds with many contemporaneous Earth-based stellar occultations. In Paper I, we introduced two updated techniques for reanalyzing these 26 occultations—forward modeling and inversion—and demonstrated them on the 1977 Uranus occultation. This work (Paper II) presents the results of applying these techniques to 26 total Uranus stellar occultations, observed between 1977 and 1996. We find that the lower thermosphere of Uranus is much cooler than the Voyager 2 profiles but slightly warmer than the originally published occultations. We find that the stratosphere of Uranus is nearly isothermal and the stratosphere–thermosphere boundary is much higher in altitude than previously believed. Furthermore, we present a family of new, one-dimensional atmospheric models for Uranus fit to our results. The models suggest that there is a significant source of heat transport or dissipation away from the stratosphere, which we discuss as resulting from gravity-wave activity. We offer our models as new representative profiles and discuss how they improve the understanding of the energy balance of Uranus.